Effectiveness of insect egg removal device in controlling insect progeny development in stored grains - Hategekimana, Athanase; Mohan, Sarma (Fundamental and Applied Agriculture, 2020)
The side effects of pesticides and fumigants have led to the development of ecofriendly stored grains in insect management methods. Insect egg remover is one of the recent inventions to be used in the management of stored grain insects. The inner brushing arrangement in the device facilitates the crushing of the eggs, if any, in the grains. Investigations were made to determine the effectiveness of the insect egg remover for the management of stored grain insects. The number of times the grains passed in the device (one, two and three times) and the density of insects (10, 20 and 30) were the two factors of the experiment. After rotating the grains with eggs in the machine, they were incubated for 60 days for assessing progeny production and grains damage. The device proved effective in reducing the emergence of Rhyzopertha dominica (F) and Tribolium castaneum (Herbst) adults without the influence of the densities of insects artificially introduced in paddy and sorghum grains, respectively. The pattern of emerged adults was significantly less in three passes. In addition, the density of insects did not influence significantly the emergence of adults and grain damage. However, grains damage at 40 and 60 days of incubation was significantly affected by the number of passes in the device. The lowest damage was recorded in three passes and the highest damage was in untreated grains. Most farmers could benefit by using this mechanical device. The design of the device is such that it can facilitate in crushing eggs beside the rapid removal of adult insects from mild and severely infested grains and consequently prevent grains damage and eliminates the possibility of the pests developing resistance over time. However, the machine has the limitations of controlling only external feeding stored insects and this study recommends a cost-benefit analysis.